Pengaruh Efektivitas dan Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Demak - ulyana, wahdaul; Ningsih, Tri Widyastuti (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this study was to determine the level of effectiveness and contribution of local tax revenues and their effect on Regional Original Income in Demak Regency in 20112020. This study uses data collection techniques through documentation, namely secondary data in the form of Budget Realization Reports and Demak Regency. Data management is done by calculating the ratio of each variable, namely the effectiveness of local taxes, local tax contributions, and local revenue. Then it is calculated and processed using the Statistical Product and Service Solution (SPSS) software program. Based on the results of the effectiveness and contribution ratio analysis, it shows the effectiveness of the Demak Regency regional tax during the years 2011-2020, with an average of 131.738% and belongs to the very effective criteria. The contribution of local taxes to the local revenue of Demak Regency during 2011-2020 is with an average of 35.244% and is included in the criteria quite well. The effectiveness of local taxes partially has a significant effect on PAD in Demak Regency and the contribution of local taxes partially does not have a significant effect on PAD in Demak Regency. Simultaneously, the effectiveness of local taxes and local tax contributions has no significant effect on PAD in Demak Regency.